Dual retrotympanic aural mass - Che Ab Rahim, Nurul Asma (BMJ Case Rep, 2021)
High-riding jugular bulb (HRJB), although rare, may pose a challenge as it may be mistaken for other non-alarming condition, such as middle ear effusion. Patients with HRJB classically present with pulsatile tinnitus. We report a unique case of a 26-year-old patient with underlying beta thalassaemia who presented with a 2-month history of intermittent epistaxis and rhinorrhoea. Otoscopic examinations revealed a pulsatile bluish mass behind the right tympanic membrane and a dull left tympanic membrane. Imaging performed revealed a finding of dual retrotympanic pathology, which consisted of a right dehiscent HRJB and left cholesterol granuloma. We highlight a rare case of dual retrotympanic mass as well as its management.